Developing Animal Model for Analysing Liver Toxicity of Isoniazid and Rifampicin Combination - I Gusti Ayu Artini (Journal of Global Pharma Technology, 2016)
Background: Liver toxicity often results from drug administration, such as antituberculosis. The prevalence of liver toxicity in tuberculosis patients remained high in the last decade. Liver toxicity induced by isoniazid (INH) and rifampicin (RIF) combination might have different features and mechanisms with liver toxicity induced by other substances or drugs (acetaminophen, carbontetrachloride, d-galactosamine, ethanol or dimethylnitrosamine). The goal of this study was to investigate the toxic dose and duration of administration of combined isoniazid and rifampicin that contributed to the hepatic injury in rats. Methods: A combination of INH-RIF contained 100 mg of INH and 100 mg of RIF. The induction of INH-RIF was given for 28 consecutive days. Twenty rats were divided into five groups: control, group 1 (dose 50 mg), group 2 (dose 100 mg), group 3 (dose 200 mg), group 4 (dose 400 mg),and group 5 (dose 800 mg). At the end of induction, serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) were measured, and liver histopathology was evaluated. Data were analyzed with one-way Anova test. Results: Serum AST and ALT levels were significantly higher in groups 1 and 2 compared to control (p<0.001). Post-hoc analysis revealed that 50 mg and 100 mg dose significantly increased the serum AST and ALT. Conclusion: There were significant differences in serum AST and ALT, as well as histopathological scores, among rats induced by INH and RIF combination.Keywords: Isoniazid; Rifampicin; Liver; Animal.